Individual match playing time during the season affects fitness-related parameters of male professional soccer players - Silva, J. R.; Magalhaes, J. F.; Ascensão, A. A.; Oliveira, E. M.; Seabra, A. F.; Rebelo, A. N. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to analyze the effects of an entire season on physical fitness parameters (PFPs) in male professional soccer players (N = 18). Performance in 5- and 30-m sprint (T5 and T30), countermovement jump (CMJ), agility (T-test), knee extensor (KE) and knee flexor (KF) isokinetic strength, hamstrings/quadriceps strength ratio (H/Q) and bilateral differences (BDs), and Yo-Yo intermittent endurance test 2 (YYIE2) was evaluated in 4 moments (E1-E4) throughout the season. Individual match playing time was quantified. Significant improvements in CMJ and YYIE2 from E1 to E2 were observed (p < 0.05-0.01). The T30 improved from E2 to E3 (p < 0.01). The CMJ decreased from E2 to E3 and E4, and YYIE2 from E2 to E4 (p < 0.05). There were increments in the H/Q ratio and Agility from E1 and E2 to E3 and E4 (p < 0.05-0.01). Significant correlations were found in all evaluation points between different PFPs and between changes in strength parameters and agility, T5 and T30, CMJ, and YYIE2 (p < 0.05-0.001). Influence of individual match playing time was correlated to changes in T5 (E1 to E3; r = -0.705), KE nondominant leg (KEND; E2 to E3; r = 0.786), and KF (E3 to E4; r = 0.575-0.590). The interrelationship between muscle strength (e.g., KE), sprint (e.g., T5), and jump abilities (CMJ) suggests the importance of muscle strength and power training for soccer. This study suggests that the systematic participation of the players in soccer matches favors the increase and maintenance of soccer players KE and KF muscle strength and sprint ability (T5). Thus, given the unique demands of actual match play, coaches should try to incorporate a competitive friendly match in the weekly training cycle of nonstarter players.